On the Margins : Jews and Muslims in Interwar Berlin - Jonker, Gerdien (2020)
This title is available in its entirety in Open Access. Living on the margins of German society, Jews and Muslims in interwar Berlin explored common ground. Based on a number of private archives, the study discusses the contact zones and personal entanglements that arose from their meeting. Readership: All interested in border crossings, the fusing of cultures and traditions, the fertile ground which margins offer, and the shared interests between Jews and Muslims in the 20th Century.